Attitude and Performance of Faculties Towards the Implementation of the Electronic Learning System (ELS) in Mashhad University of Medical Sciences (MUMS) in 2009 - Ali Vafaee Najar; Maryam Mohammadi; Behrooz Khiabani; Hossein Ibrahimpour (مجله ایرانی آموزش در علوم پزشکی, 2011)
Introduction: In recent years ETS has become a common method of training in many universities around the country but we do not have similar experiences in Medical Universities. The aim of the current study is to investigate the attitude and performance of MUMS faculties towards the implementation of ETS. Method: This descriptive – cross sectional study was carried out in 2009. The study population was faculties of MUMS (360). A stratified and randomize sampling method was used to select 86 faculties. Data gathering tool was a 38- item questionnaire. Data were analyzed using SPSS software. Result: About 65% of the study population was male and 35% female. 90.7% of faculties were completely agreed, 4.7% were totally agreed and 4.7% were totally disagreed with using ETS. About 46.5% of faculties were engaged in material preparation for the system, and 34.9% used ETS in their regular teaching courses. The common teaching methods among the faculties were lecture (3.72±1.3) and group discussion (3.47±1.07). Conclusion: Based on the positive attitude and performance of the MUMS faculties towards ETS, it is suggested that measures be taken to prepare the required infrastructure to use this system in teaching university courses.